2016
DOI: 10.1016/j.kint.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α promotes glomerulosclerosis and regulates COL1A2 expression through interactions with Smad3

Abstract: The function of hypoxia-inducible factor-1α (HIF-1α) in chronic kidney disease is disputed. Here we report that interactions of HIF-1α with transforming growth factor beta (TGF-β) signaling may promote its fibrotic effects. Knockout of HIF-1α is protective against glomerulosclerosis and glomerular type-I collagen accumulation in a mouse podocyte ablation model. Transcriptional analysis of cultured renal cells showed that α2(I) collagen expression is directly regulated by HIF-1α binding to a functional hypoxia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 68 publications
1
61
0
Order By: Relevance
“…TSP‐1 is associated with cardiac fibrosis in ischaemia and is a potent activator of TGF‐β1 . COLIA2 is a subunit of collagen that undergoes extracellular processing to become ECM and thus, contributes to fibrosis . HIF‐1α stimulates a COLIA2 promoter leading to increased accumulation of collagen subunits in human tubular epithelial cells contributing to glomerular sclerosis .…”
Section: Adipose Tissue Fibrosis and Inflammationmentioning
confidence: 99%
“…TSP‐1 is associated with cardiac fibrosis in ischaemia and is a potent activator of TGF‐β1 . COLIA2 is a subunit of collagen that undergoes extracellular processing to become ECM and thus, contributes to fibrosis . HIF‐1α stimulates a COLIA2 promoter leading to increased accumulation of collagen subunits in human tubular epithelial cells contributing to glomerular sclerosis .…”
Section: Adipose Tissue Fibrosis and Inflammationmentioning
confidence: 99%
“…Genetic manipulation of HIF-1α expression in mice has demonstrated that HIF is profibrotic in several mouse models of progressive CKD. 43,50,51 However, inhibition of HIF exacerbates injury in several other models. 5255 While it is possible that these results are model dependent, the general trend suggests that HIFs play a role in protecting the kidney against acute hypoxic injury, whereas they may play a deleterious role in more chronic, fibrotic injury.…”
Section: Mechanisms Of Renal Injury and Repair May Lead To Ckdmentioning
confidence: 99%
“…92 The decrease in mitochondria further decreases ATP generation. While the source of intracellular ROS remains somewhat controversial, 101103 one downstream mediator of ROS actions is the stabilization and generation of HIF , which promotes extracellular matrix expression 50 and decreases cell metabolic rates further. With decreased tubular function, less local generation of pro-angiogenic factors such as VEGF leads to decreased health of the peritubular vasculature, 104 further promoting hypoxia and HIF expression.…”
Section: The Tubule As a Major Determinant Of Progressionmentioning
confidence: 99%
“…Baumann et al reported, in an animal experiment, that increased HIF‐1α expression potentiates the damage caused by specific TGF‐β‐mediated kidney diseases and found a strong correlation between the COL1A2 gene‐regulating HIF‐1α in response to TGF‐β.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, HIF-1α regulates the activity of AMPK and contributes to the improvement of kidney function, which corroborates the study of Chen et al 68 Using the small interference RNA technique (SiRNA) for the HIF-1α gene, Chen et al 68 studies, these markers may interact directly with the expression of HIF. 52,68,69,74,76 Baumann et al 77 reported, in an animal experiment, that increased HIF-1α expression potentiates the damage caused by specific TGF-βmediated kidney diseases and found a strong correlation between the COL1A2 gene-regulating HIF-1α in response to TGF-β.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%